2022
DOI: 10.3390/pharmaceutics14040869
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicular Growth through Intermittent Vaginal Gonadotropin Administration in Diminished Ovarian Reserve Women

Abstract: It is a challenge to obtain enough oocytes during in vitro fertilization (IVF) in women who have a poor ovarian response (POR) in achieving conception. We have adopted the characteristics of the first uterine pass effect, which we pioneered in employing the vaginal administration of gonadotropins in women receiving IVF treatments. In our previous study employing vaginal administration, faster absorption and slower elimination of gonadotropins were demonstrated, and, female subjects presented proper ovarian fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ]. Thus, a personalized IVF treatment with fine-tuning of the Gn dose in accordance with each individual’s ovarian response has become a safe and effective practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ]. Thus, a personalized IVF treatment with fine-tuning of the Gn dose in accordance with each individual’s ovarian response has become a safe and effective practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%